2017
DOI: 10.12659/msm.898660
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-146a Ameliorates Inflammation via TRAF6/NF-κB Pathway in Intervertebral Disc Cells

Abstract: BackgroundIntervertebral disc degeneration (IDD) has been widely recognized as a major contributor to low back pain. Accumulating evidence suggests that IDD is linked to various pro-inflammatory cytokines and metabolites. Recently, numerous studies have demonstrated that microRNAs (miRNAs) play a pivotal role in the development of most disorders, including degenerative disc diseases. Previous reports have revealed that miRNA-146a (miR-146a) could attenuate neuropathic pain in the spinal cord. The aim of this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 26 publications
0
30
0
Order By: Relevance
“…A recent study suggested that overexpression of miR-146a significantly decreased the levels of pro-inflammatory cytokines, including IL-1b, TNF-α, and IL-6 by targeting the TARF6/NFκB pathway. It is indicated that miR-146a ameliorates inflammation via the TRAF6/NF-kB pathway in intervertebral disc cells 26,27 . Our results lend credence to the previous study suggesting that HCG18, acting as a miR-146a-5p sponge, accelerate IDD progression via the miR-146a-5p/TARF6/NFκB axis.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study suggested that overexpression of miR-146a significantly decreased the levels of pro-inflammatory cytokines, including IL-1b, TNF-α, and IL-6 by targeting the TARF6/NFκB pathway. It is indicated that miR-146a ameliorates inflammation via the TRAF6/NF-kB pathway in intervertebral disc cells 26,27 . Our results lend credence to the previous study suggesting that HCG18, acting as a miR-146a-5p sponge, accelerate IDD progression via the miR-146a-5p/TARF6/NFκB axis.…”
Section: Discussionmentioning
confidence: 99%
“…NF‐κB signaling activates transcription factors in response to inflammation, cellular damage, and tissue degeneration . Many reports have shown that the NF‐κB signaling pathway has an important role in IDD . Therefore, we investigated whether the RADA‐KPSS peptide could protect TNF‐α‐treated NPCs by inhibiting NF‐κB signaling.…”
Section: Discussionmentioning
confidence: 99%
“…6,40 Many reports have shown that the NF-jB signaling pathway has an important role in IDD. 41,42 Therefore, we investigated whether the RADA-KPSS peptide could protect TNF-a-treated NPCs by inhibiting NF-jB signaling. Initially, the immunofluorescence of NF-jB-p65 was detected mainly in the cytoplasm of NPCs in the presence of RADA16-I, whereas the nuclear location of p65 protein was observed in TNF-a-treated NPCs cultured with both RADA16-I and RADA-KPSS peptides.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Hu et al reported that miR-194 and miR-515 can relieve the biosynthesis of chondroitin sulfate during human IDD development (19). Lv et al suggest that miR-146a over-expression can promote IDD through regulating TRAF/NF-κB pathway (20). miR-15 has been found upregulated in IDD and it can promote IDD by targeting MAP3K9 (21).…”
Section: Discussionmentioning
confidence: 99%